Teacher Beliefs and Subject Matter Boundaries: The Struggle for Curricular Transformation Among Teachers of Adults - John M. Dirkx; Marilyn Amey; Lisa Haston (Adult Education Research Conference, 1999)
Teachers of adult learners in formal settings are increasingly exploring more integrated approaches to curriculum and teaching. One location for such work is the community college. Among these teachers, however, who are traditionally content experts, an integrated approach often represents a paradigmatic shift in their understanding of what is most worth knowing. Little is known about how these teachers' beliefs influence, change, and are changed by participation in such curriculum efforts. This study reports on the beliefs and meaning and perspectives of one group of teachers attempting to bring about more curricular coherence and integration within four different disciplines of developmental education.